Alfred Marshall, Silver, and China. (26th July 2017) - Zhao, Liuyan; Zhao, Yan
Abstract : The paper provides an empirical investigation of Alfred Marshall's analysis of the silver flow mechanism between the West and the East, which maintains that silver will flow whenever there is a difference in its purchasing power. The results show that Marshall's analysis offers an empirically sound interpretation of changes in the price level in China and the silver flow across China's borders. The results also confirm that there was a high degree of international integration for China's internal and external prices of silver. Moreover, the stable purchasing power parity could in practice be maintained by silver flow without resorting to a substantial percentage of tradable goods.